Rethinking the Mechanisms Underlying the McGurk Illusion - Gonzales, Mariel G.; Backer, Kristina C.; Mandujano, Brenna; Shahin, Antoine J. (Frontiers in Human Neuroscience, 2021)
The McGurk illusion occurs when listeners hear an illusory percept (i.e., ‘da’ or ‘ta’), resulting from mismatched pairings of auditory and visual speech stimuli (i.e., auditory /ba/ or /pa/ paired with visual /ga/ or /ka/, respectively). This illusory phenomenon of hearing a third percept, ‘da’ or ‘ta’—which is distinct from both the auditory and visual input—has been used as evidence of audiovisual (AV) fusion. If AV fusion mediates the McGurk illusion, then individuals should hear different illusory percepts for different AV combinations. To test this hypothesis, subjects were presented with silent videos (V-only) of a talker uttering various consonant vowel syllables (CVs), and the same videos paired with auditory /ba/ stimuli (AV). Individuals transcribed the syllable they saw (V-only) or heard (AV). In Experiment 1, in the V-only condition, individuals predominantly saw ‘da’/‘ta’ when viewing CVs with indiscernible places of articulation (POAs). Likewise, in the AV condition, upon perceiving an illusion, they predominantly heard ‘da’/‘ta’ for CVs with indiscernible POAs. In Experiment 2, we attempted to replicate these findings using stimuli recorded from a different talker. In the V-only condition, individuals did not favor ‘da’/‘ta’ over ‘ga’/‘ka’, unlike Experiment 1. However, Experiment 2 replicated the results of the AV condition, such that participants predominately heard ‘da’/‘ta’/‘tha’ as an illusory percept for various AV combinations. These results demonstrate that when a visual CV with an ambiguous POA is paired with auditory /ba/, listeners default to hearing ‘da’/‘ta’/‘tha’ – thus, suggesting that AV 'fusion may not underlie the McGurk illusion.